A model for continued professional development with focus on inquiry-based learning in science education - Kurtén, Berit; Henriksson, Ann-Catherine (LUMAT: International Journal on Math, Science and Technology Education, 2021)
This is a qualitative study with a twofold aim. The first aim is to describe and analyse teachers' perceptions of advantages and challenges with a model for continued professional development (CPD) for primary school teachers. The CPD course was about inquiry-based learning (IBL) in science education. The second aim of the study is to analyse the teachers' thoughts after implementing inquiry-based methods in their own science teaching. The empirical data, in the form of video transcriptions, notes, interviews and results from electronic forms, were collected during and after four separate in-service courses for teachers (N=26). The analysis of the data is done through thematic analysis. As positive results, the teachers emphasised the implementation of IBL with their students and the individual mentoring, which were parts of the CPD model. Teachers highlighted the importance of students' possibilities to make investigations based on their own questions, which proved to have a positive impact on students' interest and motivation. Teachers also saw the importance of their own planning and goal setting. The results indicate that the teachers perceived a tension between having control and relinquishing control, which can become a challenge. Two other challenges were teachers' perceived lack of time for planning and implementing but also teachers' deficient subject knowledge.